2018
DOI: 10.1113/ep087190
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of the long non‐coding RNA XIST ameliorates podocyte apoptosis in membranous nephropathy via the miR‐217–TLR4 pathway

Abstract: New Findings What is the central question of this study?What is the role of the long non‐coding RNA X‐inactive specific transcript (XIST), which is up‐regulated in injured podocytes and membranous nephropathy, in the pathogenesis of membranous nephropathy? What is the main finding and its importance?XIST was up‐regulated in kidney tissue with membranous nephropathy and in injured podocytes. Down‐regulation of XIST inhibited podocyte apoptosis. XIST negatively regulated miR‐217, and miR‐217 modulated Toll‐like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 26 publications
0
31
1
Order By: Relevance
“…Subsequently, the beads were washed 3 times in wash buffer (50 mM Tris–HCl, 300 mM NaCl pH 7.4, 1 mM MgCl 2 , 0.1% Nonidet P-40) followed by RNA extraction using the Trizol reagent (Invitrogen, USA). The expression of LSAMP-AS1 and miR-183–5p was determined by reverse transcription quantitative PCR (RT-qPCR) [29].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the beads were washed 3 times in wash buffer (50 mM Tris–HCl, 300 mM NaCl pH 7.4, 1 mM MgCl 2 , 0.1% Nonidet P-40) followed by RNA extraction using the Trizol reagent (Invitrogen, USA). The expression of LSAMP-AS1 and miR-183–5p was determined by reverse transcription quantitative PCR (RT-qPCR) [29].…”
Section: Methodsmentioning
confidence: 99%
“…In hyperglycemic condition, GAS5 inhibits the regulatory action of miR-27a towards the BCL2 Interacting Protein 3 (BNIP3), thus causing an upregulation of BNIP3 expression and renal tubular epithelial cell apoptosis (Lv et al, 2019). Another lncRNA is the lncRNA XIST, in which its expression was high in patients with primary membranous nephropathy, and this high expression of lncRNA XIST was due to Ang II treatment that promotes podocyte apoptosis (Jin et al, 2019). In this study, higher expression of lncRNA XIST inhibited the miR-217 action from suppressing the TLR4 expression; thus, leads to TRL4 activation of inflammatory and apoptosis effects (Jin et al, 2019).…”
Section: Lncrnas-mirnas Interactions In Autophagy and Apoptosismentioning
confidence: 99%
“…Another lncRNA is the lncRNA XIST, in which its expression was high in patients with primary membranous nephropathy, and this high expression of lncRNA XIST was due to Ang II treatment that promotes podocyte apoptosis (Jin et al, 2019). In this study, higher expression of lncRNA XIST inhibited the miR-217 action from suppressing the TLR4 expression; thus, leads to TRL4 activation of inflammatory and apoptosis effects (Jin et al, 2019). Interestingly, lncRNA XIST expression can be detected in the urine samples (Huang et al, 2014) thus suggesting the potential of this lncRNA as a biomarker for DN.…”
Section: Lncrnas-mirnas Interactions In Autophagy and Apoptosismentioning
confidence: 99%
“…The actual pathophysiological impact of this work remains to be determined. One of the longest-known lncRNAs—XIST, which is known for its role in the inactivation of the X-chromosome—has been linked to membranous nephropathy (MN) [48,55]. This lncRNA was found to be upregulated both in a mouse model of MN and in human samples [55].…”
Section: Lncrnas In Glomerular Diseasementioning
confidence: 99%
“…This lncRNA was found to be upregulated both in a mouse model of MN and in human samples [55]. Data in cell culture pointed towards XIST exerting its proapoptotic effect on podocytes through sequestration of miR-217 and consecutive upregulation of Toll-like receptor 4 [48]. Finally, in a recent report Liao et al showed differential expression of lncRNAs in kidney biopsies of patients diagnosed with lupus nephritis (LN) [49].…”
Section: Lncrnas In Glomerular Diseasementioning
confidence: 99%